Chile: Improving Access and Quality to Stop Social Unrest - Schiefelbein, Ernesto (International Higher Education, 2012)
Chile has faced significant student unrest, and accompanying political instability. The causes of this activism were mainly increased tuition in higher education that were imposed without any improvement in academic standards.